Specific features of bronchial inflammation in asthma patients with airway hyper-responsiveness to cold and osmotic stimuli - Aleksey B. Pirogov; Anna G. Prikhodko; Sergey V. Zinov’ev; Eugen A. Borodin; Elena V. Ushakova; Galina A. Makarova; Juliy M. Perelman (Бюллетень сибирской медицины)
Background. Excessive airway reaction to combined effects of environmental factors is very common in patients with asthma. The understanding of the molecular-cellular mechanisms of this hyperresponsiveness is very important.Aim. The aim of the work was to study granulocyte segment of bronchial inflammation in correlation with cytokine regulation and lipid peroxidation in patients with airway hyperresponsiveness to cold and osmotic stimuli.Materials and мethods. In 43 patients with partially controlled and uncontrolled persistent asthma with cold and osmotic airway hyperresponsiveness (group 1) asthma symptoms and lung function were assessed, the level of IL-5, IL-12 in exhaled breath condensate (EBC) and the total amount of myeloperoxidase (MPO) in induced sputum (IS) were measured; the number of neutrophils and eosinophils in smears of IS was counted. Basing on cytological and cytochemical analysis of smears of IS, the activity coefficients of MPO in granular leukocytes, the degree of cell destruction and the intensity of cytolysis were calculated. The contents of lipid hydroperoxide (LHP) and MPO in the blood serum were measured. A control group (group 2) consisted of asthma patients without airway reaction to cold and osmotic stimuli (11 people).Results. In the first group in comparison with the second one high levels of IL-12 were found (2,94 ± 0,09 vs. 2,53 ± 0,13 pg/mL; р = 0,024), IL-5 (3,64 ± 0,37 vs. 2,15 ± 0,14 pg/mL; р = 0,0001); the increase of neutrophils in IM (35,4 ± 3,5 vs. 17,2 ± 2,0%; р = 0,014); higher granulocytes cytolysis (0,38 ± 0,02 vs. 0,26 ± 0,02; р = 0,013), which correlated for neutrophils with the level of IL-12 (r = 0,46; р = 0,026); there was found out the increase of MPO concentration in IS (199,7 ± 49,0 vs. 81,4 ± 26,2 pixels; р = 0,039). The increased level of LHP in the blood serum correlated with the level of MPO in IS (r = 0,48; р = 0,039) and IL-5 in EBC (r = 0,71; р = 0,031).Conclusion. Airway hyperresponsiveness to cold and osmotic stimuli in patients with asthma is characterized by the relationship between the nature of Th1 and Th2 cytokine profile, the structure of granulocyte segment of bronchial inflammation, the enzymatic function of granulocytes, MPO activity and systemic formation of suboxidized lipid peroxidation products. Activation of granulocyte segment of inflammatory pattern in patients with asthma may be considered a factor of influence on the development and maintenance of airway hyperresponsiveness due to the escalation of oxidative stress and persistent inflammation.